1970
DOI: 10.19109/nurani.v18i1.1920
|View full text |Cite
|
Sign up to set email alerts
|

Bank Internal Factors and Profit Distribution Management of Syariah Banks in Indonesia

Abstract: The purpose of this study is to analyze the effect of Capital Adequacy Ratio (CAR), Operation Efficiency (BOPO), Financing to Deposit Ratio (FDR), Proportion of Depositor’s Funding (PDPK), Purchase Financing (PJB), Profit Sharing Financing (PBH) and Return On Assets (ROA) to Profit Distribution Management (PDM) in Islamic banks in Indonesia. The sample determined by using purposive sampling based on Indonesia Syariah Bank for period of 2009-2013. The population in this research is 11 Syariah Banks, which 5 Sya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Alteza (2017) revealed that if the financing incurred is high while the profit sharing obtained is low, it can make managers' motivation to carry out high-Profit Distribution Management (PDM) impossible to do, considering it will be challenging to deal with the possible risks that will arise. This study's results align with the research conducted by Mismiwati (2018), which shows that the BOPO ratio has no significant effect on Profit Distribution Management (PDM). However, research conducted by Nengsih (2020) shows that BOPO has an effect on Profit Distribution Management.…”
Section: The Effect Of Operational Income Operating Costs On Profit D...supporting
confidence: 87%
See 1 more Smart Citation
“…Alteza (2017) revealed that if the financing incurred is high while the profit sharing obtained is low, it can make managers' motivation to carry out high-Profit Distribution Management (PDM) impossible to do, considering it will be challenging to deal with the possible risks that will arise. This study's results align with the research conducted by Mismiwati (2018), which shows that the BOPO ratio has no significant effect on Profit Distribution Management (PDM). However, research conducted by Nengsih (2020) shows that BOPO has an effect on Profit Distribution Management.…”
Section: The Effect Of Operational Income Operating Costs On Profit D...supporting
confidence: 87%
“…The profit-sharing system makes the amount of profit the customer gets adhere to the amount of profit the bank gets. The distribution of customer funds collected can be placed by Islamic banks in business sectors that generate profits (Mismiwati, 2018).…”
Section: Introductionmentioning
confidence: 99%